Population genetics of Plasmodium vivax with transmission and rebound in two endemic areas of Papua New Guinea - Fola, Abebe A.; Mehra, Somya; Razook, Zahra; Lautu-Gumal, Dulcie; Nate, Elma; Lee, Stuart; Kattenberg, Johanna Helena; Koepfli, Cristian; Kazura, James; Ome-Kaius, Maria; Laman, Moses; Robinson, Leanne J.; et al. (Frontiers in Genetics, 2026)
BackgroundGlobal efforts to control and eventually eliminate malaria have been less effective for Plasmodium vivax relative to Plasmodium falciparum due to its unique biology, including dormant liver stages that cause later relapse, and earlier commitment to transmission stages. After the nationwide distribution of long-lasting insecticide treated nets (LLIN) in Papua New Guinea (PNG), P. vivax initially reduced to low prevalence, but again resurged to levels similar to those before LLIN distributions.MethodTo explore changes in P. vivax population structure and identify sources of resurgence over this period, we applied a previously validated genome-wide SNP barcode to genotype 336 P. vivax isolates obtained from serial cross-sectional surveys conducted over a decade in East Sepik (2005, 2012, 2016) and Madang Province (2006, 2010, 2014).ResultsPopulation genetic analyses of the resulting parasite genotypes revealed contrasting spatiotemporal patterns between the two provinces. In Madang, the complexity of infection, genetic diversity, and population structure varied with prevalence, with a possible population bottleneck and early clonal expansion at low transmission, and rapid recovery of the population with resurgence. In East Sepik, there was a less dramatic impact on the parasite population after prevalence decline, and ongoing transmission of multiple residual lineages throughout the study period. P. vivax decline was also accompanied by an increase in genetic differentiation between the two areas, which reduced with resurgence suggesting changes in parasite migration between areas associated with prevalence.ConclusionThe earlier implementation of LLIN in East Sepik, smaller rebound, heterogeneity in transmission and relative isolation, compared to Madang may have contributed to these differing patterns. The results demonstrate that long term sustained control efforts are essential to make a lasting impact on the P. vivax population, and that SNP barcodes can provide valuable insights into parasite transmission dynamics as a result of control efforts.